Eliciting and Analyzing Male Mouse Ultrasonic Vocalization (USV) Songs - Chabout, Jonathan (J Vis Exp, 2017)
Mice produce ultrasonic vocalizations (USVs) in a variety of social contexts throughout development and adulthood. These USVs are used for mother-pup retrieval1, juvenile interactions2, opposite and same sex interactions345, and territorial interactions6. For decades, the USVs have been used by investigators as proxies to study neuropsychiatric and developmental or behavioral disorders789, and more recently to understand mechanisms and evolution of vocal communication among vertebrates10. Within the sexual interactions, adult male mice produce USV songs, which have some features similar to courtship songs of songbirds11. The use of such multisyllabic repertoires can increase potential flexibility and information they carry, as they can be varied in how elements are organized and recombined, namely syntax. In this protocol a reliable method to elicit USV songs from male mice in various social contexts, such as exposure to fresh female urine, anesthetized animals, and estrus females is described. This includes conditions to induce a large amount of syllables from the mice. We reduce recording of ambient noises with inexpensive sound chambers, and present a quantification method to automatically detect, classify and analyze the USVs. The latter includes evaluation of call-rate, vocal repertoire, acoustic parameters, and syntax. Various approaches and insight on using playbacks to study an animal's preference for specific song types are described. These methods were used to describe acoustic and syntax changes across different contexts in male mice, and song preferences in female mice.